Mutu Fisik, Kadar Serat dan Sifat Organoleptik Nata de Cassava Berdasarkan Lama Fermentasi - Indah Putriana; Siti Aminah (Universitas Muhammadiyah Semarang, 2013)
Nata de cassava are product from cassava extract with fermentation bacteria species Acetobacter xylinum. Nata constitutes one of components in nutrients as a source of dietary fiber. Period of fermentation is one of essential factor in makings nata de cassava. The aim this research is to know physical quality, and organoleptic characteristic from nata de cassava with period time of fermentation. Thickness and yield best exists on 13th days fermentation 1,37 cm and 59,09 % respectively, meanwhile best brightness on 5th days fermentation around 64,70. Concentration of fiber is biggest in 7th days fermentation approximately 94,31 mg. Organoleptic quality perceives nata de cassava delicate on 13th day fermentation.